Over-Expression of the Heat-Responsive Wheat Gene TaHSP23.9 in Transgenic Arabidopsis Conferred Tolerance to Heat and Salt Stress - Wang, Jun; Gao, Xin; Dong, Jun; Tian, Xinyu; Wang, Junzhe; Palta, Jairo A.; Xu, Shengbao; Fang, Yan; Wang, Zhonghua (Frontiers in Plant Science, 2020)
The small heat shock proteins (sHSP) are stress-induced proteins with molecular weights ranging from 12 to 42 kDa that act as molecular chaperones to prevent the irreversible aggregation of denaturing proteins. In this study, we cloned the heat responsive gene TaHSP23.9 from wheat (Triticum aestivum) based on TMT-labeled quantitative proteomic analysis in our previous work and examined its function in the response of transgenic Arabidopsis to heat and salt stress. Amino acid alignment and phylogenetic tree analysis showed that TaHSP23.9 contained a typically conserved structure of the alpha-crystallin domain and is closely related to OsHSP23.2 in rice. Transient expression assays demonstrated that TaHSP23.9 is located on the endoplasmic reticulum. Quantitative real-time PCR demonstrated that TaHSP23.9 was expressed much more in filling grains under normal conditions and was significantly upregulated by heat and salt stress. Transgenic Arabidopsis plants that constitutively over-expressed TaHSP23.9 had no visible differences or adverse phenotypes compared with the wild type under normal conditions but exhibited enhanced tolerance to heat and salt stress under stress conditions. In addition, we found that the expression level of TaHSP23.9 was significantly higher in the heat-tolerant wheat varieties than in the heat-sensitive varieties. Our results suggest that TaHSP23.9 may function as a protein chaperone to positively regulate plant responses to heat and salt stress and could be developed as a molecular marker for screening heat-tolerant wheat varieties.